Cambering Steel Beams - Ricker, David T. (Engineering Journal, 1989)
Natural mill camber is the out-of-straightness remaining after the initial rolling, cooling, and straightening of the member at the mill. Tolerances for natural mill camber are listed in the AISC Manual of Steel Construction. Induced camber is that which is applied subsequent to the initial rolling and straightening process. Induced cambering can be done at either the rolling mill or the fabricating shop. Tolerances for induced camber are also listed in the AISC Manual of Steel Construction.